High expression of acidic chitinase and chitin digestibility in the stomach of common marmoset (Callithrix jacchus), an insectivorous nonhuman primate - Tabata, Eri; Kashimura, Akinori; Uehara, Maiko; Wakita, Satoshi; Sakaguchi, Masayoshi; Sugahara, Yasusato; Yurimoto, Terumi; Sasaki, Erika; Matoska, Vaclav; Bauer, Peter O; Oyama, Fumitaka (Scientific reports, 2019)
Chitin is a polymer of N-acetyl-D-glucosamine (GlcNAc) and a main constituent of insects' exoskeleton. Insects are rich in protein with high energy conversion efficiency. Recently, we have reported that acidic chitinases (Chia) act as digestive enzymes in mouse, pig and chicken (omnivorous) but not in dog (carnivorous) and bovine (herbivorous), indicating that feeding behavior affects Chia expression levels, and determines chitin digestibility in the particular animals. Common marmoset (Callithrix jacchus) belongs to New World monkey family and provides a potential bridge between mouse models and human diseases. Common marmoset is an insectivorous nonhuman primate with unknown expression levels and enzymatic functions of the Chia homologue, CHIA. Here, we report that common marmoset highly expresses pepsin-, trypsin- and chymotrypsin-resistant CHIA in the stomach. We show that CHIA is most active at pH 2.0 and degrades chitin and mealworm shells into GlcNAc dimers under gastrointestinal conditions. Although common marmoset and crab-eating monkey (Old World monkey) have two CHIA genes in their genomes, they primarily express one gene in the stomach. Thus, this study is the first to investigate expression levels and enzymatic functions of CHIA in a New World primate, contributing to the understanding of dietary adaptation and digestion in this taxon.
Keywords: Chitin; Callithrix; Stomach; chitinasy; stravovací zvyklosti; Animals; Chitinases; Feeding Behavior; zvířata; Diet; žaludek; dieta; chitin